Agentes biológicos e homeopatia no desenvolvimento e síntese de compostos bioativos em mudas de maracujá azedo - Trento, Rogelho Alexandre (2020)
The use of regional microorganism biodiversity is important for agriculture development, with low cost and the possibility of nutritionally improving fresh consumption crops such as passion fruit (Passiflora edulis Sims f. flavicarpa Degener). With these premises this study was carried out with objective of evaluating effects of homeopathy Calcarea carbonica 12CH, homeopathic preparation of green propolis 6CH, saprobic fungi filtrates from the Amazon Brachysporiella sp., Ellisembia sp., Gonytrichum sp., yeast filtrate Pichia sp., green propolis extract and Bacillus subtilis, in control of Lasiodiplodia rot caused by Lasiodiplodia sp.; in the development of passion fruit seedlings (Passiflora edulis Sims f. flavicarpa Degener) and plant defense mechanisms (synthesis of phenolic compounds and proteins, antioxidant enzyme activity). The experiment was conducted in a completely randomized design (CRD) with 10 treatments in a time-divided plot. Each plot was constituted by 5 plants and the data submitted to analysis of variance and when significant, compared by the Scott-Knott test (p <0.05). The evaluations described in chapters 02 and 03 were performed at 67, 74 and 82 days after transplantation (DAT). Chapter 02 describes the evaluation of variables related to plant growth, such as plant height (cm), leaf area (cm2 ), total biomass (g), root length and area under the disease progress curve (AUDPC). In chapter 03, the variables analyzed were production and quantification of total phenolics, flavonoids orientin, isoorientine, isovitexine and rutin, total proteins and anti-oxidant enzyme superoxide dismutase. In both studies, the treatments, saprobic fungi filtrate Gonytrichum sp., yeast filtrate Pichia sp., B. subtilis and homeopathy Calcarea carbonica 12CH showed the best results in development of seedlings and in synthesis of flavonoids, phenols and total proteins. It is concluded that it is possible to use saprobic fungi filtrates and bio products to improve the development of passion fruit seedlings and contribute to a better development of the productive chain of passion fruit, especially the family agriculture.